2018
DOI: 10.1158/0008-5472.can-17-3514
|View full text |Cite
|
Sign up to set email alerts
|

PHF5A Epigenetically Inhibits Apoptosis to Promote Breast Cancer Progression

Abstract: Alternative splicing (AS) and its regulation play critical roles in cancer, yet the dysregulation of AS and its molecular bases in breast cancer development have not yet been elucidated. Using an CRISPR screen targeting RNA-binding proteins, we identified PHD finger protein 5A (PHF5A) as a key splicing factor involved in tumor progression. PHF5A expression was frequently upregulated in breast cancer and correlated with poor survival, and knockdown of PHF5A significantly suppressed cell proliferation, migration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 47 publications
5
74
0
Order By: Relevance
“…To further validate the correlation of gene expression and MeGDP or MBS, we performed GPS in two breast cell lines, MCF-10A and MCF-10A-1H (Zheng et al 2018). We found the correlation between gene expression and MeGDP or MBS were consistent with the previous results (Supplemental Fig.…”
Section: Methylation Boundary Shift In the Promoter Region Modulates supporting
confidence: 87%
“…To further validate the correlation of gene expression and MeGDP or MBS, we performed GPS in two breast cell lines, MCF-10A and MCF-10A-1H (Zheng et al 2018). We found the correlation between gene expression and MeGDP or MBS were consistent with the previous results (Supplemental Fig.…”
Section: Methylation Boundary Shift In the Promoter Region Modulates supporting
confidence: 87%
“…PHF5A is a highly conserved PHD-zinc finger domain protein that facilitates interactions between the U2 snRNP complex and DNA/RNA helicases [25]. Additionally, PHF5A facilitates interactions with specific histone marks on chromatin-bound nucleosomes through its PHD domain [26][27][28][29]. PHF5A inhibition also compromised GSC tumor formation in vivo and inhibited the growth of established GBM patient-derived xenograft tumors [30].…”
Section: Discussionmentioning
confidence: 99%
“…In GBM, PHF5A was discovered to be integral for the survival of GSCs by mediating the recognition of specific exons with unusual C‐rich 3’ splice sites in thousands of essential genes . Recently, using in vivo CRISPR screening, Zheng et al identified PHF5A as a key splicing factor involved in breast cancer progression; they found that PHF5A was required for SF3b spliceosome stability and linked the complex to histones, and the PHF5A–SF3b complex modulated AS changes in apoptotic signaling pathways . However, there was no research investigating the role of PHF5A in lung cancer until a few months ago.…”
Section: Discussionmentioning
confidence: 99%